POTENSI DAYA TARIK OBYEK WISATA AIR TERJUN TIRTA ALAMI MALIBO ANAI KABUPATEN PADANG PARIAMAN SUMATERA BARAT - YEFRIDA KOGOYA KOGOYA; Yurni Suasti (JURNAL BUANA, 2023)
This study aims: 1) Knowing the natural attractions of Tirta Alami Waterfall, Kyu Tanam District. 2) know the accessibility, tourism development of Tirta Alami Waterfall District, Kayu Tanam. 3) find out Amenitis or the availability of infrastructure suggestions in natural water tourism. 4) knowing the Ancilarry Organization in the development of Tirta Alami Tourism and 5) knowing the number of visitors to Tirta Alami Tourism in 2019-2021.This type of research is a descriptive research, which is trying to reveal how the potential tourist attraction of the Tirta Natural Malibo Waterfall is. The technique of collecting data by conducting a questionnaire (questionnaire), observation, interviews and documentation. The source of data from this study used primary data obtained from direct interviews with informants, namely the community who visited the natural water tourism object. Secondary data in this study were data obtained from reading sources and various other sources. that the condition of the attractions at the Tirta Alami Tourism Object is well maintained and in terms of accessibility to go to the Tirta Alami Tourism Object, it is included in the category of easy and very easy to visit and visitor facilities are available, lodging, mosques, toilets, cafes, swimming pools, campsites, already available at this natural waters attraction will develop tourism and tourist loyalty to an increase in the number of visitors to the natural waters tourism object. costs and ticket prices for attractions t natural water is included in the cheap category. so that the price of admission is not a factor causing the decline in visitors, and in terms of service and security that the service from the ticket officer for the natural water attraction is included in the very friendly category, and security at the natural water tourist attraction is very safe.